2020
DOI: 10.1016/j.isci.2020.101477
|View full text |Cite
|
Sign up to set email alerts
|

Gut Bacterial Species Distinctively Impact Host Purine Metabolites during Aging in Drosophila

Abstract: Summary Gut microbiota impacts the host metabolome and affects its health span. How bacterial species in the gut influence age-dependent metabolic alteration has not been elucidated. Here we show in Drosophila melanogaster that allantoin, an end product of purine metabolism, is increased during aging in a microbiota-dependent manner. Allantoin levels are low in young flies but are commonly elevated upon lifespan-shortening dietary manipulations such as high-purine, high-sugar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 49 publications
10
32
0
Order By: Relevance
“…Yamauchi et al demonstrated how some bacterial species within the gut microbiome could release many metabolites and protein molecules that distinctively impact host purine levels (Yamauchi et al 2020 ). Given that enrichment of Bacteroides may be the footprint of gout disease, our work implied an understanding of the role of Bacteroides species found in the core microbiota of gouty patients.…”
Section: Discussionmentioning
confidence: 99%
“…Yamauchi et al demonstrated how some bacterial species within the gut microbiome could release many metabolites and protein molecules that distinctively impact host purine levels (Yamauchi et al 2020 ). Given that enrichment of Bacteroides may be the footprint of gout disease, our work implied an understanding of the role of Bacteroides species found in the core microbiota of gouty patients.…”
Section: Discussionmentioning
confidence: 99%
“…A chronic inflammatory condition in aged flies triggers neurodegeneration and shortens lifespan, which can be rescued by inhibition of Imd signalling in glial cells ( Kounatidis et al, 2017 ). Age-related activation of the Imd pathway in the renal (Malpighian) tubules induced by a commensal organism, Acetobacter persici , triggers age-dependent metabolic shifts, including purine metabolism ( Yamauchi et al, 2020 ). These studies have revealed that age-related immune activation in various tissues leads to organismal ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Arc1 regulates lipid homeostasis and central carbon metabolite levels in Drosophila larvae (Mosher et al, 2015), and loss of Arc1 results in enhanced adult starvation resistance (Mattaliano et al, 2007). These and other metabolic traits are also impacted by the microbiota, depending on dietary conditions and host genetic background (Dobson et al, 2015; Gnainsky et al, 2021; Judd et al, 2018; Yamauchi et al, 2020). One major consequence of GF-induced metabolic dysregulation in Drosophila is prolonged larval growth (Strigini and Leulier, 2016).…”
Section: Resultsmentioning
confidence: 99%